Determinants of postnatal care service utilization among mothers of Mangochi district, Malawi: a community-based cross-sectional study - Jonas Sagawa; Allen Kabagenyi; Godwin Turyasingura; Saul Eric Mwale (BMC Pregnancy and Childbirth, 2021)
Abstract Background Postnatal care (PNC) service is a neglected yet an essential service that can reduce maternal, neonatal and infant morbidity and mortality rates in low and middle-income countries. In Malawi, maternal and infant mortality rates remain high despite numerous efforts by the government and its partners to improve maternal health service coverage across the country. This study examined the determinants of PNC utilization among mothers in Mangochi District, Malawi. Methods A community based cross-sectional study was conducted among 600 mothers who gave birth in the past 2 years preceding January 1–31; 2016. A multistage sampling technique was employed to select respondents from nine randomly selected villages in Mangochi district. A transcribed semi-structured questionnaire was pre-tested, modified and used to collect data on socio-demographic characteristics and maternal related factors. Data was coded in EpiData version 3.1 and analysed in Stata version 12. A multivariable logistic regression adjusted for confounding factors was used to identify predictors of PNC utilization using odds ratio with 95% confidence interval and p-value of 0.05. Results The study revealed that the prevalence of PNC service utilization was 84.8%. Mother’s and partner’s secondary education level and above (AOR = 2.42, CI: 1.97–6.04; AOR = 1.45, CI: 1.25–2.49), partner’s occupation in civil service and business (AOR = 3.17, CI: 1.25, 8.01; AOR =3.39, CI:1.40–8.18), household income of at least MK50, 000 (AOR = 14.41, CI: 5.90–35.16), joint decision making (AOR = 2.27, CI: 1.13, 4.57), knowledge of the available PNC services (AOR = 4.06, CI: 2.22–7.41), knowledge of at least one postpartum danger sign (AOR = 4.00, CI: 2.09, 7.50), health facility delivery of last pregnancy (AOR = 6.88, CI: 3.35, 14.14) positively associated with PNC service utilization. Conclusion The rate of PNC service utilization among mothers was 85%. The uptake of PNC services among mothers was mainly influenced by mother and partner education level, occupation status of the partner, household income, decision making power, knowledge of available PNC services, knowledge of at least one postpartum danger signs, and place of delivery. Therefore, PNC awareness campaigns, training and economic empowerment programs targeting mothers who delivered at home with primary education background and low economic status are needed.